The role of wind, temperature and relative humidity on PM fractions in a suburban mediterranean region - Pateraki, S.a b; Asimakopoulos, D.N.b; Maggos, T.a; Flocas, H.A.b; Vasilakos, C.a (Fresenius Environmental Bulletin, 2010)
This paper evaluates the role of meteorological factors on the configuration of the complex aerosol’s character at a suburban area of Athens, Greece. To this effort, 4-month period measurements of hourly PM2.5 aerosol samples were employed, being collected with the aid of a conventional R&P TEOM (model 1400a) at Aghia Paraskevi. The simultaneous daily PM10 and PM2.5.10 concentrations are also discussed. Then, the entire daily data set was divided in 5 different classes at similar proportion by one decimal point for each one of assessed meteorological parameter, temperature, relative humidity and wind speed. The present study discusses not only the variations of the recorded levels of the three PM fractions and their seasonality but also the inter-fraction relationship for all possible matching of the aerosol’s pairs and the PM ratios in connection with the differentiation of the meteorological parameters’ values. PM10 and PM2.5-10 appeared to have the same character as in all the cases they proved to be strongly correlated. It was found that temperature enhanced the concentrations of the PM fractions and especially those with bigger diameter while relative humidity seemed to favour the formation of fine particles. Wind direction appeared to play a key role on the recorded PM profile. The transportation from the ’polluted’ Athens center proved to be the major mechanism which deters the ’clean atmosphere’ of the suburban area. © by PSP.
Keywords: aerosol; air sampling; air temperature; Athens [Attica]; atmospheric pollution; Attica; data set; Greece; Particulate matter; Relative humidity; Seasonality; suburban area; wind velocity